ТӘЛИМ СИСТЕМАСЫ СЫПАТЫН КӨТЕРИЎ - БҮГИНГИ КҮННИҢ АКТУАЛ МӘСЕЛЕЛЕРИНЕН БИРИ СЫПАТЫНДА - Пазылова, М. (FAN va JAMIYAT, 2018)
The article is devoted to the description of existing education quality assessment systems and their conditional separation into two groups based on their external or internal assessment: the French model based on the external model and the Englisn, based on internal assessments.